Associations Between High Ambient Temperature and Acute Ischemic Stroke Admissions - Wil Lieberman-Cribbin; Jason J. Wang; Bo Yang; Joseph O’Hara; Maria X. Sanmartin; Liron Sinvani; Jeffrey M. Katz; Pina C. Sanelli (International Journal of Environmental Research and Public Health, 2026)
Stroke is a leading cause of death and foremost cause of disability in the United States, and extreme heat is the leading weather-related cause of death. We examined the association between ambient temperature and acute ischemic stroke (AIS) admissions in New York State. We leveraged an existing cohort of consecutive AIS admissions presenting to a large healthcare system during a ten-year period (January 2015–December 2024), identified based on discharge diagnosis codes for ischemic stroke. Meteorological data from gridMET (~4 km grids) were used to produce daily averages of maximum temperature (Tmax) for ZIP code tabulation area (ZCTA) boundaries in the New York metropolitan area, linked to residential ZIP codes. Time-stratified case-crossover models with distributed lags (0–1 days) were used to estimate the association between daily maximum temperature (evaluated as a 10 °F increase, 95th percentile temperature vs. median temperature, and 95 °F vs. median temperature) and AIS admissions, both for the entire year and restricted to warm season months of May–October. There were 27,926 AIS admissions from 2015 to 2024. The mean (standard deviation, SD) age was 71.7 (14.4) years, and 13,934 (49.9%) were female, while the mean (SD) Tmax was 62.8 (17.3) °F, and the mean 95th percentile Tmax was 87.9 °F. The relative risk (95% confidence interval) of AIS admissions was strongest on the same day of admission (10 °F increase: 1.041 (1.019, 1.064); 95th percentile: 1.105 (1.047, 1.165); 95 °F: 1.132 (1.059, 1.210), and effects were similar in warm season months. High daily maximum temperatures were associated with an increased risk of AIS admissions, with the highest risk on the same day of admission. These findings support the short-term impact of temperature on AIS admissions and can inform future public health efforts to reduce heat-related AIS risk in affected populations.